Ceramic dispergator based on ceramic lithium slag and preparation method of ceramic dispergator
By using ceramic decomposition agent composed of cellulose nitrate, polyethylene glycol, alcohol, and diol -glycol ether acetate, the problem of lithium lithium slag in porcelain residue is easy to reunite and potassium hydroxide water absorption. The efficient decomposition and liquidity of ceramic billets are realized.
Patent Information
- Application Number
- CN202411502276.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has failed to propose a special ceramic degluing agent for ceramic manufacturing based on ceramic lithium slag, which leads to the agglomeration of ceramic lithium slag when powdered, and potassium hydroxide is prone to absorb water and dehydration, resulting in sticky mud.
Ceramide nitrate, polyethylene glycol, polyethylene glycol, alcoholic acid salt, and dioxyl ether acetate, etc., evenly dispersed through ultrasonic vibration and stirring methods to form a mixture with an unclean effect.
Effectively reduce the viscosity of the mud, improve the liquidity and stability of the mud, avoid the reunion of alumina, silicon oxide, and iron oxide, and improve the preparation efficiency and quality of ceramic billets.
Smart Images

Figure BDA0005102918440000081 
Figure BDA0005102918440000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic degumming agents, and in particular to a ceramic degumming agent based on porcelain lithium slag and a preparation method thereof. Background Art
[0002] Porcelain lithium slag is a waste product produced after lithium ore is refined. Its main components are aluminum oxide, silicon oxide, iron oxide and potassium hydroxide, which are the main raw materials for ceramic manufacturing and can be used to make ceramics. Studies have shown that after removing toxic elements such as cobalt, cadmium and lead from lithium slag, high-quality ecological ceramics made from lithium slag have good physical and chemical properties and ecological and environmental benefits, and can be widely used in daily-use ceramics, building ceramics and other fields.
[0003] As we all know, ceramic dispersants are also called ceramic water reducers, ceramic dispersants, and ceramic grinding aids. Ceramic dispersants are auxiliary chemical materials that account for a small part of the amount used in the production of ceramic products, but they play a vital role in the production process and product high quality assurance. Ceramic dispersants are mainly used in ceramic glazes and slurries. They can effectively improve the particle wettability, suspension stability and slurry rheology of glazes and slurries, and make the slurry have a suitable viscosity to achieve the purpose of energy saving and consumption reduction. Ceramic dispersants can effectively dissolve the insoluble substances in ceramic blanks, reduce the viscosity of the slurry, improve the fluidity of the slurry, and reduce the water content of the slurry, thereby effectively reducing the ball milling time of the ground body and the drying energy consumption in spray powder making, and improving the powder production output and quality; at the same time, adding an appropriate amount of dispersants to the ceramic body formula can make the particle grading of the powder produced by spray drying more reasonable, improve the fluidity of the powder, and improve and enhance the comprehensive performance of the slurry and powder.
[0004] Before using, the porcelain lithium slag needs to be crushed, ball-milled, pressed into powder, etc., so that it can be evenly mixed with other co-solvents. However, since components such as aluminum oxide, silicon oxide, and iron oxide are prone to agglomeration when in powder form, and potassium hydroxide is hygroscopic, it is easy to absorb moisture in the mud and deliquesce, making the mud sticky. In summary, since porcelain lithium slag contains a large amount of components such as aluminum oxide, silicon oxide, iron oxide, and potassium hydroxide, it is necessary to use a corresponding degumming agent to effectively degumming it, reduce the viscosity of the mud, improve the fluidity of the mud, and reduce the water content of the mud. At present, no ceramic degumming agent specifically based on porcelain lithium slag has been proposed in the existing literature. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, one of the purposes of the present invention is to provide a ceramic degumming agent based on porcelain lithium slag to solve the above-mentioned traditional technical problems.
[0006] The second object of the present invention is to provide a method for preparing the ceramic degumming agent based on porcelain lithium slag.
[0007] One of the purposes of the present invention is achieved by the following technical solution:
[0008] A ceramic debonding agent based on porcelain lithium slag, comprising the following components in parts by weight:
[0009] Cellulose nitrate 20-50 parts, polyethylene glycol 8-15 parts, tartrate 1-5 parts, diethylene glycol ethyl ether acetate 5-15 parts, water 20-30 parts.
[0010] Furthermore, cellulose nitrate is prepared by nitrating cellulose with a mixture of nitric acid and sulfuric acid, followed by deacidification, pre-washing, boiling, washing, dehydration, and then dehydration with alcohol to obtain alcohol-moist nitrocellulose.
[0011] The structural formula of nitrocellulose is
[0012] Cellulose nitrate has a large cellulose molecular structure and alcohols attached to the surface. It can adsorb aluminum oxide, silicon oxide, and iron oxide separately through the hydrogen bonding between molecules, and achieve a separation effect on each of them. It can effectively reduce the contact opportunities between aluminum oxide, silicon oxide, and iron oxide, and separate them to avoid their agglomeration.
[0013] Furthermore, polyethylene glycol can combine with cellulose nitrate due to its -OH group, further separating aluminum oxide, silicon oxide and iron oxide, and at the same time, utilizing the effects of polyethylene glycol, cellulose nitrate and diethylene glycol ethyl ether acetate, reduce the viscosity of the mud, improve the fluidity of the mud and reduce the water content of the mud. The molecular weight of the polyethylene glycol is 200-300. Low molecular weight polyethylene glycol can be used as a wetting agent and consistency regulator to adjust the fluidity of the system.
[0014] Further, the tartrate is divided into alkaline tartrate and acidic tartrate, wherein the alkaline tartrate is one or more of potassium sodium tartrate, calcium tartrate, and copper tartrate; the acidic tartrate is one or more of aluminum tartrate, zirconium tartrate, and iron tartrate. Tartrate can combine with elements such as cobalt, cadmium, lead, or other metal ions left in the porcelain lithium slag to form corresponding salts, or form soluble complexes, which is convenient for improving the stability of the degumming agent, and tartrate is also easy to obtain from nature, production impurities, etc., with low cost, so as to reduce some manufacturing costs of ceramics.
[0015] Furthermore, the mass ratio of the cellulose nitrate to the polyethylene glycol is (2.8-3.2):1, such as.
[0016] Furthermore, the mass ratio of the cellulose nitrate to the polyethylene glycol is 3:1.
[0017] Furthermore, the water is pure water.
[0018] The second object of the present invention is achieved by adopting the following technical solution:
[0019] A method for preparing a ceramic disintegrator based on porcelain lithium slag comprises the following preparation steps:
[0020] S1: dissolving diethylene glycol ethyl ether acetate in water, adding cellulose nitrate and polyethylene glycol, and dispersing them uniformly by ultrasonic vibration and stirring to obtain a mixture;
[0021] S2: Add tartrate to the mixture and stir evenly to obtain the product.
[0022] Furthermore, in step S1, the stirring speed is controlled at 10r / min-20r / min, the stirring time is 3min-8min, the vibration frequency of the ultrasonic vibration is 10kHz-20kHz, and the vibration time is 3min-8min; in step S2, the stirring speed is controlled at 10r / min-20r / min, and the stirring time is 1min-3min.
[0023] The ceramic degumming agent of the invention is ball-milled, slurried or molded together with the raw materials according to 0.2-0.6% of the dry material amount of the porcelain lithium slag blank.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The ceramic degumming agent of the present invention adopts the combination of cellulose nitrate, polyethylene glycol and diethylene glycol ethyl ether acetate. Cellulose nitrate has a large cellulose molecular structure and alcohols attached to the surface. It can adsorb and separate easily agglomerated oxides such as aluminum oxide, silicon oxide and iron oxide in porcelain lithium slag through the action of hydrogen bonds between molecules. Combined with the effects of polyethylene glycol, diethylene glycol ethyl ether acetate and other components, at the same time, by adding tartrate, it can combine with elements such as cobalt, cadmium, lead or other metal ions in porcelain lithium slag to form corresponding salts or soluble complexes, so as to reduce the viscosity of the mud, improve the fluidity of the mud, reduce the water content of the mud, and achieve a better degumming effect. DETAILED DESCRIPTION
[0026] The present invention is further described below in conjunction with specific embodiments. It should be noted that, under the premise of no conflict, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. In the embodiments, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified. The molecular weight of polyethylene glycol is 300. Cellulose nitrate is obtained by nitrating cellulose with a mixed solution of nitric acid and sulfuric acid, deacidifying, pre-washing, boiling, washing, dehydrating, and then removing water with alcohol to obtain alcohol-wet nitrocellulose. Tartrate is potassium sodium tartrate. Water is purified water.
[0027] Example 1 The mass ratio of cellulose nitrate to polyethylene glycol is 1.34:1
[0028] A ceramic debonding agent, comprising the following components in parts by weight:
[0029] 20 parts of cellulose nitrate, 15 parts of polyethylene glycol, 5 parts of tartrate, 15 parts of diethylene glycol ethyl ether acetate, and 30 parts of water.
[0030] The preparation method of the ceramic dissolving agent comprises the following preparation steps:
[0031] S1: dissolving diethylene glycol ethyl ether acetate in water, adding cellulose nitrate and polyethylene glycol, and dispersing them uniformly by ultrasonic vibration and stirring to obtain a mixture; the stirring speed is controlled at / min, the stirring time is 8min, the vibration frequency of ultrasonic vibration is 20kHz, and the vibration time is 3min;
[0032] S2: Add tartaric acid to the mixture and stir evenly to obtain the product. The stirring speed is controlled at 20 r / min and the stirring time is 3 min.
[0033] Example 2 The mass ratio of cellulose nitrate to polyethylene glycol is 2:1
[0034] A ceramic debonding agent, comprising the following components in parts by weight:
[0035] 30 parts of cellulose nitrate, 15 parts of polyethylene glycol, 1 part of tartrate, 10 parts of diethylene glycol ethyl ether acetate, and 25 parts of water.
[0036] The preparation method of the ceramic dissolving agent comprises the following preparation steps:
[0037] S1: dissolving diethylene glycol ethyl ether acetate in water, adding cellulose nitrate and polyethylene glycol, and dispersing them uniformly by ultrasonic vibration and stirring to obtain a mixture; the stirring speed is controlled at / min, the stirring time is 8min, the vibration frequency of ultrasonic vibration is 20kHz, and the vibration time is 3min;
[0038] S2: Add tartaric acid to the mixture and stir evenly to obtain the product. The stirring speed is controlled at 20 r / min and the stirring time is 3 min.
[0039] Example 3 The mass ratio of cellulose nitrate to polyethylene glycol is 2.67:1
[0040] A ceramic debonding agent, comprising the following components in parts by weight:
[0041] 40 parts of cellulose nitrate, 15 parts of polyethylene glycol, 3 parts of tartrate, 5 parts of diethylene glycol ethyl ether acetate, and 25 parts of water.
[0042] The preparation method of the ceramic dissolving agent comprises the following preparation steps:
[0043] S1: dissolving diethylene glycol ethyl ether acetate in water, adding cellulose nitrate and polyethylene glycol, and dispersing them uniformly by ultrasonic vibration and stirring to obtain a mixture; the stirring speed is controlled at / min, the stirring time is 8min, the vibration frequency of ultrasonic vibration is 20kHz, and the vibration time is 3min;
[0044] S2: Add tartaric acid to the mixture and stir evenly to obtain the product. The stirring speed is controlled at 20 r / min and the stirring time is 3 min.
[0045] Example 4 The mass ratio of cellulose nitrate to polyethylene glycol is 3.34:1
[0046] A ceramic debonding agent, comprising the following components in parts by weight:
[0047] 50 parts of cellulose nitrate, 15 parts of polyethylene glycol, 3 parts of tartrate, 5 parts of diethylene glycol ethyl ether acetate, and 25 parts of water.
[0048] The preparation method of the ceramic dissolving agent comprises the following preparation steps:
[0049] S1: dissolving diethylene glycol ethyl ether acetate in water, adding cellulose nitrate and polyethylene glycol, and dispersing them uniformly by ultrasonic vibration and stirring to obtain a mixture; the stirring speed is controlled at / min, the stirring time is 8min, the vibration frequency of ultrasonic vibration is 20kHz, and the vibration time is 3min;
[0050] S2: Add tartaric acid to the mixture and stir evenly to obtain the product. The stirring speed is controlled at 20 r / min and the stirring time is 3 min.
[0051] Example 5 The mass ratio of cellulose nitrate to polyethylene glycol is 2.8:1
[0052] A ceramic debonding agent, comprising the following components in parts by weight:
[0053] 28 parts of cellulose nitrate, 10 parts of polyethylene glycol, 3 parts of tartrate, 10 parts of diethylene glycol ethyl ether acetate, and 25 parts of water.
[0054] The preparation method of the ceramic dissolving agent comprises the following preparation steps:
[0055] S1: dissolving diethylene glycol ethyl ether acetate in water, adding cellulose nitrate and polyethylene glycol, and dispersing them uniformly by ultrasonic vibration and stirring to obtain a mixture; the stirring speed is controlled at / min, the stirring time is 8min, the vibration frequency of ultrasonic vibration is 20kHz, and the vibration time is 3min;
[0056] S2: Add tartaric acid to the mixture and stir evenly to obtain the product. The stirring speed is controlled at 20 r / min and the stirring time is 3 min.
[0057] Example 6 The mass ratio of cellulose nitrate to polyethylene glycol is 3:1
[0058] A ceramic debonding agent, comprising the following components in parts by weight:
[0059] 30 parts of cellulose nitrate, 10 parts of polyethylene glycol, 5 parts of tartrate, 12 parts of diethylene glycol ethyl ether acetate, and 25 parts of water.
[0060] The preparation method of the ceramic dissolving agent comprises the following preparation steps:
[0061] S1: dissolving diethylene glycol ethyl ether acetate in water, adding cellulose nitrate and polyethylene glycol, and dispersing them uniformly by ultrasonic vibration and stirring to obtain a mixture; the stirring speed is controlled at / min, the stirring time is 8min, the vibration frequency of ultrasonic vibration is 20kHz, and the vibration time is 3min;
[0062] S2: Add tartaric acid to the mixture and stir evenly to obtain the product. The stirring speed is controlled at 20 r / min and the stirring time is 3 min.
[0063] Example 7 The mass ratio of cellulose nitrate to polyethylene glycol is 3.2:1
[0064] A ceramic debonding agent, comprising the following components in parts by weight:
[0065] Cellulose nitrate 32 parts, polyethylene glycol 10 parts, tartrate 3 parts, diethylene glycol ethyl ether acetate 15 parts, water 25 parts.
[0066] The preparation method of the ceramic dissolving agent comprises the following preparation steps:
[0067] S1: dissolving diethylene glycol ethyl ether acetate in water, adding cellulose nitrate and polyethylene glycol, and dispersing them uniformly by ultrasonic vibration and stirring to obtain a mixture; the stirring speed is controlled at / min, the stirring time is 8min, the vibration frequency of ultrasonic vibration is 20kHz, and the vibration time is 3min;
[0068] S2: Add tartaric acid to the mixture and stir evenly to obtain the product. The stirring speed is controlled at 20 r / min and the stirring time is 3 min.
[0069] Comparative Example 1 does not contain cellulose nitrate
[0070] Compared with Example 6, Comparative Example 1 does not contain cellulose nitrate, but is replaced by water, that is, the ceramic debonding agent of Comparative Example 1 is composed of the following components in parts by weight:
[0071] 10 parts of polyethylene glycol, 5 parts of tartrate, 12 parts of diethylene glycol ethyl ether acetate, and 55 parts of water.
[0072] The other formulas and preparation methods are the same as those in Example 6 and will not be described in detail here.
[0073] Comparative Example 2 does not contain polyethylene glycol
[0074] Compared with Example 6, Comparative Example 2 does not contain polyethylene glycol, but is replaced by water, that is, the ceramic degumming agent of Comparative Example 1 is composed of the following components in parts by weight:
[0075] Cellulose nitrate 30 parts, tartrate 5 parts, diethylene glycol ethyl ether acetate 12 parts, water 35 parts.
[0076] Comparative Example 3 does not contain diethylene glycol ethyl ether acetate
[0077] Compared with Example 6, Comparative Example 3 does not contain diethylene glycol ethyl ether acetate, but uses water instead, that is, the ceramic debonding agent of Comparative Example 1 is composed of the following components in parts by weight:
[0078] Cellulose nitrate 30 parts, polyethylene glycol 10 parts, tartrate 5 parts, water 37 parts.
[0079] Performance Test:
[0080] (1) Preparation of porcelain lithium slag blank
[0081] The raw materials are slurried together according to 0.2% of the dry material amount of the porcelain lithium slag blank.
[0082] (2) Slurry fluidity test: Pour the prepared slurry into a 100 ml Tu-4 cup, let it stand for 3 seconds, and then use a stopwatch to record the time it takes for the slurry to flow out completely. Control the slurry temperature at 25°C and take the average of three measurements, which is the flow rate of the slurry.
[0083] (3) The test results are shown in Table 1 below.
[0084] Table 1
[0085]
[0086]
[0087] It can be seen from Table 1 above that, compared with Comparative Examples 1-3, the debonding agent of Examples 1-7 can improve the fluidity of the slurry, and when the water content is reduced, the fluidity is good. In addition, it is speculated that since Comparative Example 1 does not contain cellulose nitrate, the separation distance between aluminum oxide, silicon oxide and iron oxide in the ceramic body is insufficient, and some agglomeration still exists, which affects its fluidity. Since Comparative Example 2 does not contain polyethylene glycol, and cellulose nitrate is insoluble in water, it cannot completely separate aluminum oxide, silicon oxide and iron oxide, which also affects its fluidity. Comparative Example 3 does not contain diethylene glycol ethyl ether acetate, and the effect of polyethylene glycol alone is not enough to affect the viscosity of most cellulose nitrates, which also affects the viscosity of the slurry, thereby reducing the fluidity of the slurry.
[0088] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A ceramic disintegrator based on porcelain lithium slag, characterized in that: It is composed of the following components in parts by weight: Cellulose nitrate 20-50 parts, polyethylene glycol 8-15 parts, tartrate 1-5 parts, diethylene glycol ethyl ether acetate 5-15 parts, water 20-30 parts.
2. The ceramic disintegrator based on porcelain lithium slag according to claim 1, characterized in that: The cellulose nitrate is prepared by nitrating cellulose with a mixed solution of nitric acid and sulfuric acid, followed by deacidification, pre-washing, boiling, washing, dehydration, and then dehydration with alcohol to obtain alcohol-moist nitrocellulose.
3. The ceramic disintegrator based on porcelain lithium slag according to claim 1, characterized in that: The tartrate is divided into basic tartrate and acidic tartrate.
4. The ceramic disintegrator based on porcelain lithium slag according to claim 3, characterized in that: The alkaline tartrate is one or more of potassium sodium tartrate, calcium tartrate and copper tartrate.
5. The ceramic disintegrator based on porcelain lithium slag according to claim 3, characterized in that: The acidic tartrate is one or more of aluminum tartrate, zirconium tartrate and iron tartrate.
6. The ceramic disintegrator based on porcelain lithium slag according to claim 1, characterized in that: The mass ratio of the cellulose nitrate to the polyethylene glycol is (2.8-3.2):
1.
7. The ceramic disintegrator based on porcelain lithium slag according to claim 6, characterized in that: The mass ratio of the cellulose nitrate to the polyethylene glycol is 3:
1.
8. The ceramic disintegrator based on porcelain lithium slag according to claim 1, characterized in that: The water is all purified water.
9. A method for preparing a ceramic dissolving agent based on porcelain lithium slag according to any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: S1: dissolving diethylene glycol ethyl ether acetate in water, adding cellulose nitrate and polyethylene glycol, and dispersing them uniformly by ultrasonic vibration and stirring to obtain a mixture; S2: Add tartrate to the mixture and stir evenly to obtain the product.
10. The method for preparing a ceramic dissolving agent based on porcelain lithium slag according to claim 9, characterized in that: In step S1, the stirring speed is controlled at 10r / min-20r / min, the stirring time is 3min-8min, the vibration frequency of the ultrasonic vibration is 10kHz-20kHz, and the vibration time is 3min-8min; in step S2, the stirring speed is controlled at 10r / min-20r / min, and the stirring time is 1min-3min.